Gambaran Tekanan Darah serta Korelasinya Terhadap Usia di Rukun Warga 008 Keluruhan Cipondoh Makmur - Frisca Frisca; Alexander Halim Santoso; William Gilbert Satyanagara; Giovanno Sebastian Yogie; Valentino Gilbert Lumintang; Steve Vallery Ranonto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Introduction: Hypertension is one of the most common diseases in the world, and its increasing every year. Age is one of many risk factors in hypertension. As we get older, our blood vessels tend to lose some of their elasticity and become stiffer. This can put us at risk for developing high blood pressure, also known as hypertension. It's important to take care of our cardiovascular health as we age to reduce the risk of developing this condition.Purpose: To study the correlation between blood pressure and age.Method: This was a descriptive study conducted in Cipondoh Makmur, Tangerang. The non-random consecutive sampling was used as the sampling technique, and it will be presented as descriptive data. Spearman correlation tests were used to correlate blood pressure and age if the data distribution is not normal.Result: There were 103 individuals who met the criteria, with an average age of 51.71 (12.80) years, mean systolic blood pressure of 126.2 (22.25) mmHg, and mean diastolic blood pressure of 74.46 (11.49) mmHg. A significant correlation between age and systolic blood pressure was observed (p-value: 0.001; r: 0.323, indicating a weak association), while no significant correlation was found between age and diastolic blood pressure.Conclusion: The physiological aging process is an unavoidable risk factor for hypertension. It is crucial to Increase awareness about the importance of a healthy lifestyle and optimal hypertension control.